FEATURES OF THE USE OF STYLISTIC DEVICES IN ENGLISH AND UZBEK BASED ON PRIDE AND PREJUDICE BY JAMES AUSTIN - Lobar Ibragimova Daniyorovna (PEDAGOGS, 2024)
Annotation: This article provides information about Features of the use of stylistic devices in English and Uzbek based on Pride and Prejudice by James Austin.